Nagmaal deur die eeue - ’n Oorsig van hoofbeskouinge en gebruike - Heystek, N. P. (Koers, 1990)
Holy Communion throughout the ages - A review of the main views and customs. When examining the various views on and customs of the Holy Communion from 115 B.C. up to now, two main identifiable trends, namely the symbolic and the realistic tradition will soon be discovered. All views of and customs on Holy Communion can be reduced to one of the above two trends. Of the two traditions, the symbolic tradition is the older. However, in both traditions a variation of nuances can be traced. It has been found that the line 0/ development of the symbolic tradition, which was elaborated via Augustinus, Luther, Calvin and the Reformed Confessions, is based on the Bible. The realistic tradition can also be traced back to a very early date and mainly found acceptance in the Roman Catholic Church. It has however been found that this tradition is not based on the Bible.